Efficacy of alpelisib with rational use of metformin in HR+/HER2- advanced breast cancer patients with PIK3CA mutations (m): retrospective analysis in routine practice of several Russian centers - D. A. Filonenko; R. V. Orlova; M. I. Gluzman; A. A. Vakhitova; A. Yu. Goryainova; K. S. Grechukhina; I. I. Bykonya; L. G. Zhukova (Сибирский онкологический журнал)
Background. Hyperglycemia (HG) is an on-target effect of ALP, and prophylactic with metformin was shown to decrease the rate and severity of HG. Here we present efficacy and safety of ALP in a large cohort of patients with rational approach to metformin usage based on risk factors of HG. Material and Methods. Patients (pts) with HR+/HeR2- PIK3CAmut ABC were treated with ALP 300 mg orally and FUL 500 mg IM until disease progression or intolerance. the primary endpoints were progression free survival (PFS) and rate of grade 3/4 HG in different risk groups. Pts were stratified to risk groups of HG based on the algorithm before starting ALP and received MET for prevention of HG. Results. a cohort comprised 139 pts. the median PFs (mPFS) on ALP – was 7.0 (CI 95 %: 5.0–8.9). the risk of HG was assessed in 138 pts: low (47), moderate (46), and high (42) risk, and 3 pts with type 2 diabetes mellitus. any grade HG was reported in 62 % pts, no cases HG G4 were detected. HG G3 was reported in 13 % pts; 10 % pts required ALP dose reduction to 250 mg due to HG G3; 3 pts (2 %) discontinued ALP due to HG. the mPFS in our analysis was longer than in BYlieve trial in cohort C: 7.0 vs 5.6 mo. We suggest that prophylactic of HG allowed maintenance of full dose of ALP in most patients and thus increased the efficacy of ALP. Furthermore, in contrast to the METALLICA trial we distinguished a low risk group (33 %) of pts who do not need the prophylactic use of MET. Conclusion. Rational use of MET in pts with moderate and high risk of HG reduces the frequency and severity of HG, decreases the rate of ALP dose reductions and as a result may increase the efficacy of ALP. Pts with low risk of HG don’t need MET for HG prevention.